Antimicrobial Use in Cats in a University Veterinary Hospital in Central Italy: A Retrospective Study - Matilde Vernaccini; Lucia De Marchi; Angela Briganti; Ilaria Lippi; Veronica Marchetti; Valentina Meucci; Luigi Intorre (MDPI AG, 2024)
Background: Monitoring antimicrobial use is crucial for understanding current prescribing practices. Such information helps in establishing stewardship programs for effectively using antimicrobials and combating resistance to them. Objectives: This study describes how antimicrobials are prescribed at the Veterinary Teaching Hospital of the University of Pisa and compares how the internal medicine and intensive care units differ in their usage of antimicrobials. Methods: The study involved cats that were presented in the units in 2021 and 2022. Antimicrobial prescriptions were obtained via the hospital's management software (OCIROE). Results: In a population of 1164 non-surgical cats with 397 antimicrobials prescribed, the most prescribed ones were amoxicillin-clavulanic acid in the internal medicine unit and ampicillin in the intensive care unit. Twenty-five percent of all antimicrobials were Highest-Priority Critically Important Antimicrobials or Antimicrobial Advice Ad Hoc Expert Group Category B. The oral route was the main route of administration in the internal medicine unit, while parenteral was the most common route used in the intensive care unit. Most antimicrobials were prescribed to treat pathologic conditions affecting the urinary (39%), gastroenteric (21%), respiratory (13%), and integumentary (12%) systems. A diagnosis, accurate dosage, and the use of species-approved medications were recorded in the antimicrobial prescriptions. However, only 11% of these prescriptions were supported by antimicrobial susceptibility tests. Conclusions: These results suggest room for improvement, particularly in increasing the use of antimicrobial susceptibility testing to ensure more targeted antimicrobial therapy. Given the importance of antimicrobial resistance and the One Health approach, the study also highlights the need to consider the broader impact of antimicrobial use in animals, including the potential contribution to resistance in bacteria that affect both animal and human health.